A new thermoresponsive polymer with reactive aldehyde groups for postmodification to tune the solubility and phase transition temperature. (3rd January 2019) - Huang, Jianbing; Chen, Xu; Qin, Herong; Liang, Hui; Lu, Jiang
Abstract: We first report a new thermoresponsive homopolymer with reactive functional groups in the backbone. A well-defined thermoresponsive polymer poly(2-(2-(diethylamino)ethoxy)-5-vinylbenzaldehyde) (PDEVB) with diethylamino groups and reactive aldehyde groups in each repeating unit was synthesized via reversible addition-fragmentation chain transfer polymerization. PDEVB shows lower critical solution temperature (LCST) in ethanol/water mixture. The influences of solvent composition, molecular weight, concentration on the LCST were also investigated. Thanks to the reactive aldehyde groups, the solubility and LCST behavior can be conveniently tuned by postmodification with 2-aminoethanol and 3-(aminooxy)propan-1-amine via imine formation reaction or oxime formation reaction, respectively. The obtained polymer exhibits LCST at a relatively higher water content after modification with 2-aminoethanol and becomes water soluble and shows a pH-responsive LCST after modification with 3-(aminooxy)propan-1-amine. Moreover, the PDEVB can serve as a scaffold for preparation of UCST-type polyelectrolyte via the combination of quaternization of diethylamino groups and anion exchanged with NaBF4, and the UCST of the polyelectrolyte can be tuned by postmodification of the reactive aldehydes as well. PDEVB is anticipated to be a useful novel thermoresponsive polymer and may have promising new applications. Graphical abstract: Highlights: A new thermoresponsive homopolymer with reactive aldehyde groups along the backbone was synthesized. The homopolymer PDEVB shows LCST in alcohol/water mixture. The solubility and LCST can be conveniently tuned via aldehyde-relevant reactions. PDEVB can serve as a scaffold for preparation of UCST-type polyelectrolyte.